Estratégias competitivas, uma questão atemporal: como se dá o processo de desenvolvimento das vantagens competitivas pelas startups de Uberlândia? - Silva, Sérgio Schwetter (2021)
For companies, regardless of size or segment, the topic of competitive advantages is always present as a way to generate distinction and superior and sustainable results. This theme is timeless and behaves like a race without a finish line, as the market is dynamic, and competitors continue to seek to surpass themselves and win in an increasingly competitive and rapidly changing world. In this recent past, a new configuration of companies that are Startups has become very popular, with a fundamentally technological basis, with a scalable and repeatable business model that normally proposes to transform the markets and impact the world through an innovative solution. But what is the reason for this atypical and usually very rapid success? How do these companies build and maintain their competitive advantages? What makes them unique and so special with such distinct competitive advantages that are capable of transforming the market in which they operate? Thus, the objective of this research is to identify how the competitive advantage development process takes place by Startups in Uberlândia and whether they use any theoretical framework or other means for the development of their competitive advantages. For this, a secondary data survey was carried out through a bibliometric study of the theme, considering the main theoretical approaches developed by the academy in the last 40 years and the method proposed by Endeavor and semi-structured interviews were conducted with entrepreneurs of Startups that obtained results and also with those who have not achieved relevant results, in order to identify how this process takes place. The main findings were that the Startups of Uberlândia, even without using the theoretical and academic grounds in a conscious way, build their competitive advantages based on the practices and recommendations existing in academic theories and, the ones that were more successful, were the ones that were more appropriate. of this theoretical framework, thus demonstrating that the business arrangement called Startup, also follows the model proposed in organizational management theories. It was also identified that the more mature and successful Startup, the more it behaves like a traditional company and follows good academic management practices.